THE EFFECT OF DBT THERAPY AND TAZKIYAH AL NAFSON IMPULSIVE SMOKING BEHAVIOR IN STUDENTS - Luluk Azizah; Najhan Haque; Rendika Ikhsan R; Agnes Fatimah Salwa; Dea Narenda Oktapia; Dhania Putri Hartono; Neng Nurhasanah (CV. Doki Course and Training, 2024)
Research on impulsivity and smoking shows that smokers are generally more impulsive than non-smokers and that impulsivity is associated with smoking initiation, maintenance, quitting, and nicotine dependence. Therefore, this study aims to determine the effect of BDT (dialectical behavior therapy) and Tazkiyah al-Nafs therapy on reducing impulsivity in active smokers among UIN Raden Fattah Palembang students. The type of research used in this study is qualitative research, and the participants in this study are active smoking students who have successfully quit smoking for at least 24 hours (one day). Two men were randomly selected as participants. This study used observation and interview techniques and consisted of five sessions, each session lasting 30-45 minutes. None of the two participants only quit smoking for 1-3 days (0%), but there was one participant each who managed not to smoke in 4-7 days (50%) and more than 7 days (50%). This result also indicates more success than the previous study where only 86% (6 out of 7 people) quit smoking for at least 24 hours. Despite the limitations, this study was successful in integrating the two types of therapy, and applying them well to help participants in their quit attempts.